Long term conservation of embryonic axes of genipap accessions - Nascimento, Cyntia Maia do; Oliveira, Leila Albuquerque Resende de; Silva, Ana Veruska Cruz da; Castro, Evaristo Mauro de; Lédo, Ana da Silva (Scientia Plena, 2020)
The ex situ conservation of seeds in cryobanks demands previous studies of dehydration procedures for the adjustment of the adequate moisture that makes long-term conservation possible. The objective of this work was to evaluate the effect of dehydration time on the regenerative capacity of embryonic axes of two genipap accessions (Umbaúba and Núcleo Bandeirante). Seeds were submitted to desiccation in policarbonate box containing silica gel for 0, 12, 16 and 20 h at room temperature and after each period, seed moisture content was determined. Seeds were inoculated in germination medium and samples were inserted into cryotubes and immersed in liquid nitrogen (-196ºC). Desiccation in silica gel was efficient in reducing the moisture content in both accessions. Umbaúba accession presented 100% germination at all desiccation treatments before cryopreservation and Núcleo Bandeirante was more sensitive to desiccation with 10% germination in 20 h. Umbaúba accession showed a reduction of growth variables with increased desiccation time. The treatments tested did not affect the growth variables of Núcleo Bandeirante accession. The desiccation, although changes observed in the ultra-structures of embryonic axis, did not influence the regeneration percentage of cryopreserved accessions.